Assessment of drought effect in cultivars of perennial switchgrass (Panicum virgatum L.) based on elementomic analysis and chemometrics - Molas, María Lía (2022)
Panicum virgatum L. (switchgrass) is a perennial warm season native grass from North American prairies, which is used as forage due its adaptability to grow in semi-arid regions. In this work, the assessment of response to drought in two cultivars of contrasting behavior under water stress -Kanlow and Greenville cultivars- was performed. The aim was to evaluate the behavior of both Panicum cultivars under water stress conditions based on elementomic study and chemometrics. Plants of 50 days old were grown in a growth chamber; drought treatment was applied by water suppression until a moderate stress was reached. Multi-elemental analysis was performed by inductively coupled plasma atomic emission spectrometry (ICP-AES). Elemental profile data was analyzed by chemometrics methods including Principal Component Analysis (PCA) as unsupervised method and Partial least square discriminant analysis (PLS-DA) as supervised method. Remarkable differences were found based on elementomic study in both cultivars, reinforcing the ability of Kanlow to grown in semi-arid regions, where water and saline limitations are recurrent components. However, the high concentration of Pb found in Greenville samples, shows the ability of this cultivar to be used in the recovering of contaminated soils. Moreover, two elements (Si and Zn) were identified as potential markers to discriminate switchgrass samples belonging to different cultivars or geographic origin. Panicum virgatum cv. Kanlow is a good candidate to incorporate as forage crop in semi-arid regions; however cv. Greenville can be more recommendable to be used in the recovering of Pb contaminated soils.